Cellobiose-induced B-galactosidase and B-glucosidase activities of Neurospora crassa. - P. J. Russell; C. B. Perry (Fungal Genetics Reports, 1980)
Cellobiose-induced B-galactosidase and B-glucosidase activities of Neurospora crassa.